Kad Kredit: Satu Ulasan Dari Perspektif Syariah - Sanep Ahmad; Surtahman Kastin Hasan (Universiti Sains Islam Malaysia, 2024)
Credit card is substitute of money used as medium of exchange. Its usage creates controversy not only because it encourages debt but also because the existence of questionable issues of whether its contract is in accordance to the Islamic Law as well as the persistence existence of ambiguous elements in it. If credit card is to be used it is more appropriate if its contract be based of kafalah contract, or even better if it is being replaced with debit card which is clearly avoiding the consumer from debt as well as helping in planning consumer’s current expenditure.